Apparent Reactivity of Bromine in Bromochloramine Depends on Synthesis Method: Implicating Bromine Chloride and Molecular Bromine as Important Bromine Species - Brodfuehrer, Samuel H; Goodman, Jacob B; Wahman, David G; Speitel, Jr, Gerald E; Katz, Lynn E (Journal of environmental engineering (New York, N.Y.), 2022)
The chloramination of bromide containing waters results in the formation of bromine containing haloamines: monobromamine (NH Br), dibromamine (NHBr ), and bromochloramine (NHBrCl). Many studies have directly shown that bromamines are more reactive than chloramines in oxidation and substitution reactions with organic water constituents because the bromine atom in oxidants is more labile than the chlorine atom. However, similar studies have not been performed with NHBrCl. It has been assumed that NHBrCl has similar reactivity as bromamines with organic constituents in both oxidation and substitution reactions because NHBrCl, like bromamines, rapidly oxidizes N,N-diethyl-p-phenylenediamine. In this study, we examined the reactivity of NHBrCl with phenol red to determine if NHBrCl reacts as readily as bromamines in an isolated substitution reaction. NHBrCl was synthesized two ways to assess whether NHBrCl or the highly reactive intermediates, bromine chloride (BrCl) and molecular bromine (Br ), were responsible for bromine substitution of phenol red. NHBrCl was found to be much less reactive than bromamines with phenol red and that BrCl and Br appeared to be the true brominating agents in solutions where NHBrCl is formed. This work highlights the need to reexamine what the true brominating agents are in chloraminated waters containing bromide.